A Saussurean Semiotic Analysis of a Public Service Advertisement on Indonesia’s Digital Television Migration - Prilani; Lukman Hakim; Zamzam Rahma Sofiyyana (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
This study examines how verbal, visual, and institutional signs construct persuasive meanings in a public service advertisement (PSA) promoting Indonesia’s migration from analog to digital television. The study analysed the PSA video “Yuk, Beralih ke TV Digital” uploaded by the Ministry of Communication and Information Technology (Kominfo) on YouTube using a qualitative Saussurean semiotic framework. Eleven scenes were segmented by timestamp, and observable signifiers were interpreted in relation to their associated signified concepts and persuasive functions. The analysis identified five meaning structures: analog television as a problem, digital migration as technically simple, digital broadcasting as accessible and subscription-free, digital television as modern and beneficial, and governmental authority as a source of policy legitimacy. The study analyses meaning construction in the advertisement rather than campaign effectiveness or audience reception.